HILBERT-LSB-C as Authentication System for Color Medical Images - Syifak Izhar, Hisham; Jasni, Mohamad Zain; Nurul Wahidah, Arshad; Siau-Chuin, Liew (2015)
This paper proposes a new numbering method for a fragile watermarking algorithm aimed at improving color medical image watermarking. The proposed method uses Hilbert pattern numbering before watermarking operations such as parity bits check and comparison between average intensities as the authentication data. The authentication data embedded in the same host image are utilized to localize any tamper using block-wise approach. The method is very effective since it only requires a secret key and public, chaotic mixing algorithm to recover the attacked image. We use the Hilbert mapping approach, which is more compatible with medical image modalities, which is not only specifically to the square shape of image but applicable to all kinds and modalities of the image. We propose the algorithm to match the criterion of having 3 planes in a color image. The peak-signal-noise-ratio value of the proposed scheme is very good, achieving up to 56 decibelf.